Research on Longitudinal Dynamics Simulation Technology of Automatic Driving of Heavy Haul Train - Qiao NING; Tiebing LI; Sheng HUO; Yiping YANG; Baolin ZHU (机车电传动)
In order to ensure the stability of automatic train operation, the longitudinal impact force of multiple mass points should be fully considered. This paper studied relevant contents of the longitudinal dynamics of heavy-duty train, including the modeling and simulation technology of multi-point model, air brake model and coupler buffer model, and developed the longitudinal dynamics simulation software for automatic driving. Compared with the actual operation, the test results show that the developed longitudinal dynamics software of heavy-duty train can accurately simulate the actual operation conditions of the train, which has an important guiding value for the automatic driving and smooth operation of heavy-duty train.